2019
DOI: 10.3389/fphar.2019.00698
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activities and Cellular Changes Induced by TrkB Inhibition in Medulloblastoma

Abstract: Neurotrophins are critically involved in regulating normal neural development and plasticity. Brain-derived neurotrophic factor (BDNF), a neurotrophin that acts by binding to the tropomyosin receptor kinase B (TrkB) receptor, has also been implicated in the progression of several types of cancer. However, its role in medulloblastoma (MB), the most common type of malignant brain tumor afflicting children, remains unclear. Here we show that selective TrkB inhibition with the small molecule compound ANA-12 impair… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…It is worth noting that differences in results obtained with different cell lines may be related to distinct origins and biological features. For example, D283-MED cells, which produce tumors in mice that respond to TrkB inhibition [111], are representative of Group 3/4 MB and derive from a metastatic site [113]. Studies have begun to uncover molecular differences between MB metastases and primary tumors [114].…”
Section: Bdnf and Trkbmentioning
confidence: 99%
See 3 more Smart Citations
“…It is worth noting that differences in results obtained with different cell lines may be related to distinct origins and biological features. For example, D283-MED cells, which produce tumors in mice that respond to TrkB inhibition [111], are representative of Group 3/4 MB and derive from a metastatic site [113]. Studies have begun to uncover molecular differences between MB metastases and primary tumors [114].…”
Section: Bdnf and Trkbmentioning
confidence: 99%
“…MB cell lines express both BDNF and TrkB [109,110], and TrkB blockade by the selective inhibitor ANA-12 can induce a pronounced inhibition of survival and viability, as well as cell cycle arrest, in cell lines (D283-MED and UW-228) associated with different MB molecular subgroups. In addition, we have recently shown that TrkB inhibition slows the growth of D283-MED MB tumors xenografted into nude mice in vivo, increased apoptosis, reduced ERK activity, increased expression of signal transducer and activator of transcription 3 (STAT3), and resulted in differential modulation of p21 expression [111] ( Figure 2). However, TrkB activation by BDNF may also reduce cell viability under certain experimental conditions, either when given to MB cells alone [109] or combined with a histone deacetylase inhibitor [112].…”
Section: Bdnf and Trkbmentioning
confidence: 99%
See 2 more Smart Citations
“…NTRK2 was shown to serve as an oncogene in multiple cancers (19)(20)(21)(22), and its increased expression was associated with poor outcome (23,24). Based on this, inhibition of NTRK2-encoded TRKB was shown to induce antitumor effects and cellular apoptosis (25,26). Similar to NTRK1, NTRK3 has been demonstrated to be an oncogene in breast cancer and gastric cancer (27,28), but it acts as a tumor suppressor gene in CRC, neuroblastomas, and head and neck squamous cell carcinoma (10,29,30).…”
Section: Introductionmentioning
confidence: 99%